A quantitative 3D intravital look at the juxtaglomerular renin-cell-niche reveals an individual intra/extraglomerular feedback system - Arndt, Patrick; Sradnick, Jan; Kroeger, Hannah; Holtzhausen, Stefan; Kessel, Friederike; Gerlach, Michael; Todorov, Vladimir; Hugo, Christian (Frontiers in Physiology, 2022)
The juxtaglomerular niche occupied by renin cells (RCN) plays an important role in glomerular repair but the precise temporal and spatial interrelations remain unclear. This study proposes the hypothesis of a local intra-extraglomerular regenerative feedback system and establishes a new quantifiable system for RCN responses in individual glomeruli in vivo. A strictly intraglomerular two-photon laser-induced injury model was established. Labeled renin cells (RC) in transgenic renin reporter mice were fate-traced in healthy and injured glomeruli over several days by intravital microscopy and quantified via new three-dimensional image processing algorithms based on ray tracing. RC in healthy glomeruli demonstrated dynamic extraglomerular protrusions. Upon intraglomerular injury the corresponding RCN first increased in volume and then increased in area of dynamic migration up to threefold compared to their RCN. RC started migration reaching the site of injury within 3 hours and acquired a mesangial cell phenotype without losing physical RCN-contact. During intraglomerular repair only the corresponding RCN responded via stimulated neogenesis, a process of de novo differentiation of RC to replenish the RCN. Repeated continuous intravital microscopy provides a state-of-the-art tool to prove and further study the local intraglomerular RCN repair feedback system in individual glomeruli in vivo in a quantifiable manner.